Metabolic syndrome therapy in pediatric age — between classic and modern. From diets to pipeline drugs - Frăsinariu, Otilia Elena; Lupu, Vasile Valeriu; Trandafir, Laura Mihaela; Streanga, Violeta; Jechel, Elena; Bararu-Bojan, Iris; Vasiliu, Ioana; Cuciureanu, Magdalena; Loghin, Isabela Ioana; Mitrofan, Costica; Nedelcu, Alin Horatiu; Knieling, Anton; et al. (Frontiers in Nutrition, 2024)
The metabolic syndrome, made up of the sum of the entities that define it (obesity, hypertension, dyslipidemias and non-alcoholic hepatic steatosis) has gained an important place in the research of the last decades. This aspect is mainly due to the complexity of management in pediatric practice. The main directions in his approach therefore bring together the concern of counteracting the noise or systemic, of the multiple intercurrents at the physiopathological level, as well as the negative imprint exerted on the quality of life. Its appearance and evolution are currently controversial topics, but the influence of genetic predisposition and lifestyle (diet, physical activity, psychological balance) are certainties. Considering the escalation of the incident at the global level, it is self-evident that it is necessary to know the pathogenesis and practice countermeasures for prophylactic or therapeutic purposes. The present work aims to summarize general aspects related to the metabolic syndrome encountered in pediatric age, with an emphasis on complementary therapeutic perspectives and their effectiveness, by analyzing the latest data from the specialized literature, accessed with the help of international databases (e.g. PubMed, Web of Science, Scopus, Embase, Google Scholar).